The State of Air Quality: Pollution Sources, Health Implications, and Future - Vaishnavi Joshi (International Journal of Atmosphere, 2024)
Air quality is a critical component of environmental health, significantly affecting human well-being and ecological balance. Poor air quality has been related to a variety of health issues, including respiratory and cardiovascular disorders, and it is a major cause of early death worldwide. Understanding the origins, kinds, and impacts of air pollutants is critical for establishing effective pollution-reduction initiatives. This review focuses on the principal pollutants that affect air quality, such as particulate matter (PM), ozone (O₃), nitrogen oxides (NOx), sulfur dioxide (SO₂), carbon monoxide (CO), and volatile organic compounds. Particulate matter, particularly PM2.5 and PM10, is a major concern because of its capacity to penetrate deeply into the lungs and into the bloodstream, causing serious health problems. Ozone, while beneficial in the stratosphere, poses serious health risks at ground level, where it can aggravate asthma and other respiratory conditions. Nitrogen oxides and sulfur dioxide, which are predominantly created during combustion processes, contribute to the creation of smog and acid rain, lowering air quality and hurting ecosystems. We analyze the sources of these pollutants, both from anthropogenic activities—such as industrial emissions, agricultural practices, and urban transport—and natural processes, including wildfires and volcanic eruptions. Industrial activities release a significant amount of pollutants, while agriculture contributes through the use of fertilizers and pesticides, which release ammonia and VOCs into the atmosphere. Urban transport, predominantly reliant on fossil fuels, is a major contributor to NOx, CO, and particulate matter, necessitating immediate action to mitigate its impact on air quality. The dispersion and transport mechanisms of these pollutants are complex and influenced by meteorological conditions, topography, and land use. Understanding these mechanisms is crucial for predicting air quality patterns and developing effective management strategies. Temperature inversions, for example, can trap pollutants near the ground, exacerbating air quality difficulties in cities. Furthermore, wind patterns can transport contaminants across vast distances, harming areas far from their source. Moreover, the paper highlights the implications of atmospheric deposition and phenomena like acid rain. Atmospheric deposition occurs when pollutants settle to the ground, leading to soil and water contamination, which can adversely affect flora and fauna. Acid rain, caused by the interaction of sulfur dioxide and nitrogen oxides with water vapor, is a severe hazard to aquatic ecosystems and can harm infrastructure.
Keywords: Air pollution regulations; Air quality; Atmospheric deposition; Health effects; Nitrogen oxides; Particulate Matter; Pollution mitigation; Sulfur dioxide; Volatile organic compounds; ozone